From Yugoslavia to Bosnia and Herzegovina – the impact of mutual relations on contemporary communication - Buras-Marciniak, Anetta; Goźdź-Roszkowski, Stanisław (Specialized Languages in Intercultural Communication, 2020)
Bosnia, declared independence in March 1992, which was one of the reasons for the outbreak of a civil war regarded as the bloodiest conflict in Europe since the end of World War II. The war ended in 1995 with the signing of the peace treaty in Dayton under which Bosnia and Herzegovina became an independent country, divided into two parts: Republika Srpska (49% of the territory) and the Muslim-Croatian Federation (51% of the territory). In later years, the District of Brčko was established, inhabited by the three nations. The division has had a negative impact not only on political stability in the state, but also on the entire social life. Considering the Slavic origin of all the nations that once inhabited Yugoslavia, it was established that its national culture is characterized by a large distance of power, a high degree of collectivism, dominant feminine values and a high level of risk avoidance. Religious diversity in B&H (Bosnians – Islam, Serbs – Orthodoxy, Croats – Catholicism), significantly affects not only its national culture but also the intercultural communication within the country. The aim of the article is to explain how the effects of the last war affect contemporary intercultural communication in B&H.